AMP‐activated protein kinase activator AICAR attenuates hypoxia‐induced murine fetal growth restriction in part by improving uterine artery blood flow. (6th July 2020) - Lane, Sydney L.; Houck, Julie A.; Doyle, Alexandrea S.; Bales, Elise S.; Lorca, Ramón A.; Julian, Colleen G.; Moore, Lorna G.
Abstract : Key points: Pregnancy at high altitude is associated with a greater incidence of fetal growth restriction due, in part, to lesser uterine artery blood flow. AMP‐activated protein kinase (AMPK) activation vasodilates arteries and may increase uterine artery blood flow. In this study, pharmacological activation of AMPK by the drug AICAR improved fetal growth and elevated uterine artery blood flow. These results suggest that AMPK activation is a potential strategy for improving fetal growth and raising uterine artery blood flow in pregnancy, which may be important in pregnancy disorders characterized by uteroplacental ischaemia and/or fetal hypoxia. Abstract: Uteroplacental hypoxia is associated with pregnancy disorders such as intrauterine growth restriction and preeclampsia, which are characterized by uteroplacental ischaemia and/or fetal hypoxia. Activation of AMP‐activated protein kinase (AMPK) results in vasodilatation and is therefore a potential therapeutic strategy for restoring uteroplacental perfusion in pregnancy disorders. In this study, C57Bl/6 mice were treated with subcutaneous pellets containing vehicle, the AMPK activator AICAR (200 mg kg −1 day −1 ), or the AMPK inhibitor Compound C (20 mg kg −1 day −1 ) beginning on gestational day 13.5, and were exposed to hypoxia starting on gestational day 14.5 that induced intrauterine growth restriction. Pharmacological AMPK activation by AICAR partially prevented hypoxia‐induced fetal growth restriction ( P < 0.01), due in part to increased uterine artery blood flow ( P < 0.0001). The proportion of total cardiac output flowing through the uterine artery was increased with AICAR in hypoxic mice ( P < 0.001), suggesting that the vasodilator effect of AICAR was selective for the uterine circulation. Further, pharmacological inhibition of AMPK with Compound C reduced uterine artery diameter and increased uterine artery contractility in normoxic mice, providing evidence that physiological levels of AMPK activation are necessary for vasodilatation in healthy pregnancy. Two‐way ANOVA analyses indicated that hypoxia reduced AMPK activation in the uterine artery and placenta, and AICAR increased AMPK activation in these tissues compared to vehicle. These findings provide support for further investigation into the utility of pharmacological AMPK activation for treatment of fetal growth restriction. Key points: Pregnancy at high altitude is associated with a greater incidence of fetal growth restriction due, in part, to lesser uterine artery blood flow. AMP‐activated protein kinase (AMPK) activation vasodilates arteries and may increase uterine artery blood flow. In this study, pharmacological activation of AMPK by the drug AICAR improved fetal growth and elevated uterine artery blood flow. These results suggest that AMPK activation is a potential strategy for improving fetal growth and raising uterine artery blood flow in pregnancy, which may be important in pregnancy disorders characterized by uteroplacental ischaemia and/or fetal hypoxia.